Teknik modifikasi ekstraoral radiografi Newman dan Friedman sebagai alternatif radiografi intraoral periapikal pada masa pandemi COVID-19 - Indri Kusuma Dewi; Suhardjo Sitam (Ikatan Radiologi Kedokteran Gigi Indonesia, 2020)
Objectives: This review is aimed to propose a method that could be an alternative in taking intra-oral radiographs during the COVID-19 pandemic. Literature Review: The COVID-19 pandemic is the most concerning health problem in the world today. The transmission of COVID-19 is through direct or close contact with infected secretions or aerosol droplets. Individuals with COVID-19 may be asymptomatic or presymptomatic (20%-86% of all infections). Thus, patients with undiagnosed COVID-19 can come to dental clinics and Oral and Maxillofacial Radiology centers anytime. The Oral and Maxillofacial Radiology centers from dental clinics can be a source of transmission of COVID-19 to operator and dental patients. In extraoral radiography modification technique of Newman and Friedman, the sensor is placed on the cheek outside of the oral mucosa, so that the sensor does not contact the mucosal fluid from the patient. Conclusion: Newman and Friedman's extraoral radiography modification techniques can be use as an alternatives to periapical intraoral radiographs to minimize the transmission of COVID-19.